2021
DOI: 10.1007/s10096-021-04169-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of anti-SARS-CoV-2 serological assays in a high-prevalence setting

Abstract: Evaluation and power of seroprevalence studies depend on the performed serological assays. The aim of this study was to assess four commercial serological tests from EUROIMMUN, DiaSorin, Abbott, and Roche as well as an in-house immunofluorescence and neutralization test for their capability to identify SARS-CoV-2 seropositive individuals in a high-prevalence setting. Therefore, 42 social and working contacts of a German super-spreader were tested. Consistent with a high-prevalence setting, 26 of 42 were SARS-C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 21 publications
1
42
1
1
Order By: Relevance
“…By contrast, only a weak correlation between NAbs and anti-SARS-CoV-2 IgA antibodies (Euroimmun, Lübeck) was detected for both assays (cell culture assay: r = 0.55, sVNT assay: r = 0.32, see supplement). While data for the sVNT assay are lacking, a recent study of Müller et al has already shown a good correlation between a cell culture-based NAb assay and anti-SARS-CoV-2 IgG BAb ratios determined by using the Euroimmun ELISA assay [9]. As opposed to our data, the authors also showed a good correlation to anti-SARS-CoV-2 IgA antibody results.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…By contrast, only a weak correlation between NAbs and anti-SARS-CoV-2 IgA antibodies (Euroimmun, Lübeck) was detected for both assays (cell culture assay: r = 0.55, sVNT assay: r = 0.32, see supplement). While data for the sVNT assay are lacking, a recent study of Müller et al has already shown a good correlation between a cell culture-based NAb assay and anti-SARS-CoV-2 IgG BAb ratios determined by using the Euroimmun ELISA assay [9]. As opposed to our data, the authors also showed a good correlation to anti-SARS-CoV-2 IgA antibody results.…”
Section: Discussioncontrasting
confidence: 98%
“…The experimental procedure was performed as specified by the manufacturer [8]. The cell culture assay was performed as previously described [9]. In brief, a virus stock solution with the SARS-CoV-2 NRW-42 isolate (EPI ISL 425126 [10]) was added to a final concentration of 1000 TCID50/well to heat-inactivated and diluted plasma samples.…”
Section: Resultsmentioning
confidence: 99%
“…The ECLIA technique has a good accuracy [3,49,50] and has been recommended for population screening [51]. Anti-SARS-CoV-2 antibodies obtained by ECLIA positively correlate with neutralising antibodies, but their sensitivity should be improved [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…15 Numerous enzyme-linked immunosorbent assay (ELISA) kits to detect antibodies against SARS-CoV-2 are available on the market. Although recent studies demonstrated that there is a good correlation between the immunoglobulin G (IgG) titers, 16,17 a classical neutralization assay is still the method of choice to determine the antiviral activity of serum or plasma antibodies against SARS-CoV-2. 18 According to an EU guidance for COVID-19 convalescent plasma collection and transfusion, it is strongly recommended that defined SARS-CoV-2 neutralizing antibody titers be measured in the donated plasma.…”
Section: Introductionmentioning
confidence: 99%